Implementation of translation techniques, use of software and image editing in legal documents - Gómez Jiménez, Katerin Yessenia
The translation process goes beyond the exchange of ideas from the source language to the target language. It requires a deep analysis of what is to be conveyed, the type of technique it is convenient to use, the purpose, and the audience it is addressed to. Each document has its own relevance, so each one must be treated professionally and with due respect toward its final recipient. Therefore, in this document we present a compilation of important translated documents, from English to Spanish and vice-versa, the ones we worked with throughout the specialization course, including, translated images, a birth, marriage, and divorce certificate, a university transcript, a diploma, and a protocol of agreement. We chose the right process of translation with seven important steps: reading the text, analysis, and research, translation, taking a break, comparing the two versions, editing and proofreading, and final review. In addition, the new era requires the use of different software such as Pixlr, Photopea, Cat tools that help to speed up long translation files and facilitates image editing. Despite being a complex job, it is gratifying to see the result of hours of work, and the ability we have now to transmit into our mother tongue those ideas that were originally written in a foreign language. A professional translator must be able to make the reader perceive the text as the original, not as a text that has undergone a process of transformation, a good translator is one who remains invisible to the reader's eyes.